Early Postoperative Safety of Total Hip Arthroplasty in Systemic Lupus Erythematosus Patients - YANG Xingdong; YU Muyang; XU Yiming; ZHU Wei; HU Mingwei; WENG Xisheng; FENG Bin (Xiehe Yixue Zazhi)
ObjectiveTo analyze the occurrence of early complications after total hip arthroplasty (THA) in patients with systemic lupus erythematosus (SLE).MethodsThe data of patients who underwent THA at Peking Union Medical College Hospital from June 2012 to April 2024 were retrospectively and consecutively collected. The patients were categorized into SLE group and control group based on the presence or absence of SLE. Using propensity score matching, we matched patients in the two groups at a 1∶1 ratio according to gender, age, and surgical side. Subsequently, we compared the clinical characteristics, incidence of major complications within 30 days postoperatively, and allogeneic blood transfusion rates between the two groups.ResultsA total of 270 patients in the SLE group who met the inclusion and exclusion criteria were selected. Within 30 days postoperatively, 18 cases (6.67%) experienced major complications, including 2 cases (0.74%) of upper respiratory tract infection, 2 cases (0.74%) of pulmonary infection, 3 cases (1.11%) of urinary tract infection, 2 cases (0.74%) of other systemic infection, 5 cases (1.85%) of poor wound healing, 1 case (0.37%) of wound infection, 1 case (0.37%) of gastrointestinal complications, 1 cases (0.37%) of shock, and 1 case (0.37%) of SLE flare-up. The allogeneic blood transfusion rate was 22.59% (61/270). After propensity score matching, 163 cases from SLE and control groups were included for analysis. (1) Regarding medical complications, compared with control group, SLE group showed significant differences in osteoporosis, respiratory system disorders, gastrointestinal diseases, urinary system disorders, hematologic abnormalities, and secondary or concomitant rheumatic diseases (all P < 0.05). (2) In terms of preoperative laboratory tests, SLE group had lower platelet counts, absolute lymphocyte counts, hemoglobin levels, hematocrit, albumin levels, blood glucose levels, and activated partial thromboplastin times than control group, while C-reactive protein, erythrocyte sedimentation rate, and D-dimer levels were higher (all P < 0.05). (3) Regarding surgical-related indicators, a higher proportion of patients in SLE group had an ASA grade > 2 (15.95% vs. 3.07%, P < 0.001), but intraoperative blood loss was significantly smaller [324.7 (200.0, 500.0) mL vs. 421.8 (200.0, 500.0) mL, P=0.005]. (4) In terms of complications, SLE group exhibited a significantly higher incidence of major complications than control group (8.59% vs. 1.23%, P=0.005), with a relative risk of 1.081 (95% CI: 1.028-1.136). No significant difference was observed in the allogeneic blood transfusion rate between SLE group and control group (25.77% vs. 17.18%, P=0.059).ConclusionsThe incidence of major complications within 30 days following THA in patients with SLE was significantly higher than that in non-SLE patients, while the rate of allogeneic blood transfusion remained comparable. To ensure the safety of THA surgery for patients with SLE, it is important to optimize the patient's condition and achieve stabilization prior to surgery. Additionally, strict perioperative management must be forced.